A lead-acid battery negative electrode active material and preparation method thereof

By introducing molybdenum disulfide and paste liquid into the negative electrode active material of lead-acid battery, the problem of decreasing battery capacity and life caused by negative electrode vulcanization is solved, and higher battery capacity and battery life are achieved.

CN115763748BActive Publication Date: 2025-03-18JIESHOU HUAYU POWER SUPPLY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211484997.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-24
Publication Date
2025-03-18
Estimated Expiration
2042-11-24

AI Technical Summary

Technical Problem

The negative vulcanization of lead-acid battery cells leads to a decrease in battery capacity and battery life.

Method used

A lead-acid battery negative electrode active material is used, including mixed lead powder, barium sulfate, lignin, carbon black, molybdenum disulfide and paste liquid. The paste is composed of polytetrafluoroethylene and styrene-butyl acrylate copolymer, forming a crosslinking network to reduce water loss and acts as an ion exchange resin to ensure electron transfer.

Benefits of technology

By introducing molybdenum disulfide and paste liquid, the battery capacity and battery life of lead-acid batteries are improved, the overpotential is reduced and the hydrogen evolution current is increased.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a lead-acid battery negative electrode active material and a preparation method thereof, belonging to the technical field of battery negative electrode materials, including the following raw materials by mass: 95-105 parts of mixed lead powder, 0.1-0.5 parts of barium sulfate, 0.1-0.5 parts of lignin, 0.05-0.15 parts of carbon black, 0.05-0.15 parts of molybdenum disulfide and 10-30 parts of paste liquid; its preparation method comprises the following steps: adding mixed lead powder, barium sulfate, lignin, carbon black and molybdenum disulfide to the paste liquid in sequence and stirring evenly to obtain a paste; placing the paste on a grid for curing to obtain a cured plate; electrolytically oxidizing the cured plate and reducing it in a sulfuric acid solution to form a lead-acid battery negative electrode active material. By introducing molybdenum disulfide into the lead-acid battery negative electrode active material, the discharge capacity and cycle life of the lead-acid battery are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery negative electrode materials, and in particular, relates to a lead-acid battery negative electrode active material and a preparation method thereof. Background Art

[0002] Lead-acid batteries are a common type of battery. Lead-acid batteries refer to batteries whose electrodes are mainly made of lead and its oxides, and whose electrolyte is sulfuric acid solution, which can convert chemical energy into electrical energy. Lead-acid batteries have a series of advantages such as stable voltage, low price, high safety, long life, and good performance, making them an advantage in chemical power sources and have been widely used.

[0003] However, the disadvantages of lead-acid batteries are also obvious. For example, when the negative plate is stored at a low power level for a long time, is frequently over-discharged, is undercharged for a long time, or is not charged in time, a dense and hard white lead sulfate layer will gradually accumulate on the surface of the negative plate. Not only will its solubility drop significantly, making it difficult to participate in the reaction, but it will also block the contact channel between the electrolyte and deep active substances, thereby causing a decrease in battery capacity and battery life. Summary of the invention

[0004] The purpose of the present invention is to provide a lead-acid battery negative electrode active material and a preparation method thereof, which solves the problem of reduced battery capacity and battery life caused by lead-acid battery negative electrode sulfidation in the prior art.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A lead-acid battery negative electrode active material, comprising the following raw materials in parts by weight: 95-105 parts of mixed lead powder, 0.1-0.5 parts of barium sulfate, 0.1-0.5 parts of lignin, 0.05-0.15 parts of carbon black, 0.05-0.15 parts of molybdenum disulfide and 10-30 parts of paste liquid;

[0007] The paste is obtained by mixing polytetrafluoroethylene and styrene-divinylbenzene copolymer in a mass ratio of 2-3:1. Polytetrafluoroethylene can form a cross-linked network and has strong hydrophobicity. The electrolyte has poor wettability to it, so it can diffuse oxygen and hydrogen along the cross-linked network in the negative electrode, reducing the water loss phenomenon of the lead-acid battery. However, polytetrafluoroethylene itself has insulating properties, so adding styrene-butyl acrylate copolymer as an ion exchange resin can enable electrons to be normally transferred during the charge and discharge process of the lead-acid battery.

[0008] Furthermore, the mixed lead powder is obtained by mixing lead oxide and free lead in a mass ratio of 73:27.

[0009] Furthermore, the cream is prepared by the following specific steps:

[0010] Step A1. Under nitrogen protection, add ammonium perfluorooctanoate, styrene, butyl acrylate and acrylic acid into water, mix well, then add ammonium persulfate, react at 80° C. for 0.5 h to obtain a styrene-butyl acrylate copolymer, wherein ammonium perfluorooctanoate is used as an emulsifier and ammonium persulfate is used as an initiator to initiate the copolymerization of styrene and butyl acrylate, wherein acrylic acid is easily copolymerized on the particle surface, which can improve the crosslinking and adhesion of the copolymer emulsion.

[0011] Step A2: adding polytetrafluoroethylene and sulfuric acid solution to the prepared styrene-butyl acrylate copolymer, and stirring to obtain a paste.

[0012] Furthermore, in step A1, the mass ratio of water, ammonium perfluorooctanoate, styrene, butyl acrylate, acrylic acid and ammonium persulfate is 38-44:2.5-5:48-49:48-49:2-4:0.6-0.8.

[0013] Furthermore, the water in step A1 is soft water with a conductivity of 1-3 μS / cm to avoid excessive residue content that affects battery quality.

[0014] Furthermore, in step A2, the mass ratio of the sulfuric acid solution to the styrene-butyl acrylate copolymer is 3.9-4.7:10-12, and the mass fraction of the sulfuric acid solution is 50%.

[0015] A method for preparing a negative electrode active material for a lead-acid battery comprises the following steps:

[0016] Step B1, adding mixed lead powder, barium sulfate, lignin, carbon black and molybdenum disulfide to the paste solution in sequence and stirring evenly to obtain a paste;

[0017] Step B2, placing the prepared paste on a grid for curing to obtain a cured plate;

[0018] Step B3, electrolytically oxidizing the cured plate and reducing it in a dilute sulfuric acid solution to form a negative electrode active material for a lead-acid battery.

[0019] Furthermore, the concentration of the dilute sulfuric acid solution in step B3 is 20-25%.

[0020] Beneficial effects of the present invention:

[0021] The present invention introduces molybdenum disulfide into the negative electrode active material of the lead-acid battery. Since molybdenum disulfide has a wider interlayer spacing, it has a greater ion storage capacity and ion mobility, and has catalytic activity for hydrogen evolution reaction. Therefore, the negative electrode active material of the lead-acid battery containing molybdenum disulfide exhibits a lower overpotential and a higher hydrogen evolution current, so that the battery capacity of the lead-acid battery is improved;

[0022] The present invention introduces polytetrafluoroethylene and styrene-butyl acrylate copolymer into the negative electrode active material of the lead-acid battery simultaneously with the paste. On the one hand, since polytetrafluoroethylene can form a cross-linked network and has strong hydrophobicity, the electrolyte has poor wettability to it, so that oxygen and hydrogen can be diffused along the cross-linked network in the negative electrode, thereby reducing the water loss phenomenon of the lead-acid battery. On the other hand, the styrene-butyl acrylate copolymer, as an ion exchange resin, makes up for the influence of the insulation of polytetrafluoroethylene itself on electron transfer during the charge and discharge process of the lead-acid battery, thereby greatly improving the battery life and battery capacity of the lead-acid battery. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1

[0025] A method for preparing a cream, comprising the following steps:

[0026] Step A1, under nitrogen protection, add 0.07 g of ammonium perfluorooctanoate, 1.38 g of styrene, 1.38 g of butyl acrylate and 0.06 g of acrylic acid to 1.09 g of water, mix well, then add 0.02 g of ammonium persulfate, react at 80° C. for 0.5 h, to obtain a styrene-butyl acrylate copolymer, wherein the water is soft water with a conductivity of 1 μS / cm;

[0027] Step A2: add 6 g of polytetrafluoroethylene and 1.56 g of sulfuric acid solution to the prepared styrene-butyl acrylate copolymer, and stir to obtain a paste.

[0028] Example 2

[0029] A method for preparing a cream, comprising the following steps:

[0030] Step A1, under nitrogen protection, 0.14 g of ammonium perfluorooctanoate, 2.76 g of styrene, 2.76 g of butyl acrylate and 0.12 g of acrylic acid were added to 2.18 g of water, mixed evenly, and then 0.04 g of ammonium persulfate was added, and the mixture was reacted at 80° C. for 0.5 h to obtain a styrene-butyl acrylate copolymer, wherein the water was soft water having a conductivity of 2 μS / cm;

[0031] Step A2: add 12 g of polytetrafluoroethylene and 3.13 g of sulfuric acid solution to the prepared styrene-butyl acrylate copolymer, and stir to obtain a paste.

[0032] Example 3

[0033] A method for preparing a cream, comprising the following steps:

[0034] Step A1, under nitrogen protection, 0.21 g of ammonium perfluorooctanoate, 4.14 g of styrene, 4.14 g of butyl acrylate and 0.18 g of acrylic acid were added to 3.27 g of water, mixed evenly, and then 0.06 g of ammonium persulfate was added, and the mixture was reacted at 80° C. for 0.5 h to obtain a styrene-butyl acrylate copolymer, wherein the water was soft water having a conductivity of 3 μS / cm;

[0035] Step A2: add 18 g of polytetrafluoroethylene and 4.7 g of sulfuric acid solution to the prepared styrene-butyl acrylate copolymer, and stir to obtain a paste.

[0036] Example 4

[0037] A method for preparing a negative electrode active material for a lead-acid battery comprises the following steps:

[0038] Step B1, add 95g of mixed lead powder, 0.1g of barium sulfate, 0.1g of lignin, 0.05g of carbon black and 0.05g of molybdenum disulfide to 10g of the paste (prepared in Example 1), and stir to obtain a paste;

[0039] Step B2, placing the obtained paste on a grid for curing to obtain a cured plate;

[0040] Step B3: electrolytically oxidize the cured plate and reduce it in a 20% sulfuric acid solution to form a negative electrode active material for a lead-acid battery.

[0041] Example 5

[0042] A method for preparing a negative electrode active material for a lead-acid battery comprises the following steps:

[0043] Step B1, add 100g of mixed lead powder, 0.3g of barium sulfate, 0.3g of lignin, 0.1g of carbon black and 0.1g of molybdenum disulfide to 20g of the paste (prepared in Example 2), and stir to obtain a paste;

[0044] Step B2, placing the obtained paste on a grid for curing to obtain a cured plate;

[0045] Step B3: electrolytically oxidize the cured plate and reduce it in a 22.5% sulfuric acid solution to form a negative electrode active material for a lead-acid battery.

[0046] Example 6

[0047] A method for preparing a negative electrode active material for a lead-acid battery comprises the following steps:

[0048] Step B1, add 105g of mixed lead powder, 0.5g of barium sulfate, 0.5g of lignin, 0.15g of carbon black and 0.15g of molybdenum disulfide to 30g of the paste (prepared in Example 3), and stir to obtain a paste;

[0049] Step B2, placing the obtained paste on a grid for curing to obtain a cured plate;

[0050] Step B3: electrolytically oxidize the cured plate and reduce it in a 25% sulfuric acid solution to form a negative electrode active material for a lead-acid battery.

[0051] Comparative Example 1

[0052] Compared with Example 4, this comparative example only replaces "0.05g molybdenum disulfide" with "0.05g carbon black", and the remaining raw material formulas and preparation steps are the same, which will not be repeated in this comparative example, and finally a negative active material for a lead-acid battery is obtained.

[0053] Referring to GB / T22473-2008 "Lead-acid batteries for energy storage", the lead-acid negative active materials prepared in Example 4 and Comparative Example 1 were assembled into negative plates and positive plates with sizes of 24 cm × 14 cm × 3 mm and 24.5 cm × 14.5 cm × 3.5 mm, respectively, for battery capacity testing. The two groups of fully charged batteries were discharged at room temperature (25-30°C) at a constant current of I = 15A to a termination voltage of 10.8 V. Since the battery discharge capacity is the product of the discharge current and the discharge time, the discharge time of the two groups of batteries was compared, and the specific test results are shown in Table 1 below.

[0054] Table 1

[0055] Group Discharge time / min Example 4 652 Comparative Example 1 664

[0056] It can be seen from the data in Table 1 that the battery capacity of the lead-acid battery containing molybdenum disulfide is increased by 2% compared with the lead-acid battery without molybdenum disulfide. This is because molybdenum disulfide has a wider interlayer spacing, and thus has a greater ion storage capacity and ion mobility, and has catalytic activity for hydrogen evolution reaction. Therefore, the negative electrode active material of the lead-acid battery containing molybdenum disulfide exhibits a lower overpotential and a higher hydrogen evolution current, so that the battery capacity of the lead-acid battery is improved.

[0057] Comparative Example 2

[0058] Compared with Example 6, this comparative example only replaces "30g and paste liquid" with "30g sulfuric acid solution with a mass fraction of 50%), and the remaining raw material formulas and preparation steps are the same, which will not be repeated in this comparative example, and finally a negative active material for a lead-acid battery is obtained.

[0059] Referring to the IEC60896 test standard for lead-acid batteries, the lead-acid negative active materials prepared in Example 6 and Comparative Example 2 were assembled into negative plates and positive plates with sizes of 24 cm×14 cm×3 mm and 24.5 cm×14.5 cm×3.5 mm, respectively, for battery durability testing. Both groups of batteries were immersed in a water bath at 40°C and continuously charged for 2000 h at a current of I=15 A, as shown below: (a) 2 times of 300 h charging, followed by a discharge test; (b) 3 times of 200 h charging, followed by a discharge test; (c) 8 times of 100 h charging, followed by a discharge test. At the end of each charging cycle, the lead-acid batteries were tested and discharged 10 times at a termination voltage of 11.1 V to determine the initial capacity of the lead-acid batteries. The specific test results are shown in Table 2 below.

[0060] Table 2

[0061]

[0062]

[0063] It can be seen from the data in Table 2 that, compared with lead-acid batteries without polytetrafluoroethylene, the average battery capacity of lead-acid batteries containing polytetrafluoroethylene is increased by 5.3%. On the one hand, polytetrafluoroethylene can form a cross-linked network and has strong hydrophobicity, and the electrolyte has poor wettability to it, so it can diffuse oxygen and hydrogen along the cross-linked network in the negative electrode, reducing the water loss phenomenon of the lead-acid battery. On the other hand, styrene-butyl acrylate copolymer, as an ion exchange resin, makes up for the influence of the insulation of polytetrafluoroethylene itself on electron transfer during the charge and discharge process of the lead-acid battery, thereby greatly improving the battery life and battery capacity of the lead-acid battery.

[0064] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0065] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A lead-acid battery negative electrode active material, characterized in that: The method is composed of the following raw materials in parts by weight: 95-105 parts of mixed lead powder, 0.1-0.5 parts of barium sulfate, 0.1-0.5 parts of lignin, 0.05-0.15 parts of carbon black, 0.05-0.15 parts of molybdenum disulfide and 10-30 parts of paste liquid; The paste is obtained by mixing polytetrafluoroethylene and styrene-butyl acrylate copolymer in a mass ratio of 2-3:1; The cream comprises the following specific steps: Step A1, under nitrogen protection, add ammonium perfluorooctanoate, styrene, butyl acrylate and acrylic acid into water, mix well, then add ammonium persulfate, react at 80° C. for 0.5 h, to obtain a styrene-butyl acrylate copolymer; Step A2, adding polytetrafluoroethylene and sulfuric acid solution to the prepared styrene-butyl acrylate copolymer, stirring to obtain a paste; The mass ratio of water, ammonium perfluorooctanoate, styrene, butyl acrylate, acrylic acid and ammonium persulfate in step A1 is 38-44: 2.5-5: 48-49: 48-49: 2-4: 0.6-0.8; The mass ratio of the sulfuric acid solution to the styrene-butyl acrylate copolymer in step A2 is 3.9-4.7:10-12, and the mass fraction of the sulfuric acid solution is 50%.

2. A lead-acid battery negative electrode active material according to claim 1, characterized in that: The mixed lead powder is obtained by mixing lead oxide and free lead in a mass ratio of 73:

27.

3. A lead-acid battery negative electrode active material according to claim 1, characterized in that: The water in step A1 is soft water with an electrical conductivity of 1-3 μS / cm.

4. The method for preparing a negative electrode active material for a lead-acid battery according to claim 1, characterized in that: The specific steps include: Step B1, adding mixed lead powder, barium sulfate, lignin, carbon black and molybdenum disulfide to the paste in sequence and stirring evenly to obtain a paste; Step B2, placing the prepared paste on a grid for curing to obtain a cured plate; Step B3, electrolytically oxidizing the cured plate and reducing it in a dilute sulfuric acid solution to form a negative electrode active material for a lead-acid battery.

5. The method for preparing a negative electrode active material for a lead-acid battery according to claim 4, characterized in that: The concentration of the dilute sulfuric acid solution in step B3 is 20-25%.

Citation Information

Patent Citations

  • Lead-acid storage battery negative electrode lead paste and preparation method thereof

    CN113540424A